PENEGAKAN HUKUM PIDANA TERHADAP PENCURIAN KELAPA SAWIT DI WILAYAH HUKUM POLRES KABUPATEN INDRAGIRI HULU - Aldean Dipa Damanik; Mukhlis R; Syaifullah Yophi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The crime of theft is regulated in CHAPTER XXII of the Criminal Code (KUHP). Theperpetrators of theft are charged under Article 364 of the Criminal Code as a misdemeanourwith a maximum imprisonment of 3 months or a maximum fine of two million and five hundredthousand rupiahs. Firmer law enforcement against perpetrators of criminal acts of stealingand or harvesting plantation products is regulated in Law no. 39 of 2014 concerningplantations.The type of legal research used by the author is sociological legal research. Thissociological research is a type of research in terms of legal objectives.From the results of the study, it was found that law enforcement against the crime of palmoil theft in the Inhu Resort Police area has not run optimally because several efforts made bythe Inhu Resort Police such as preventive and repressive efforts have not been able to runoptimally. In addition, there is still recognition of a peaceful settlement in which the peacefulsettlement carried out by the local community has not been able to create a deterrent effect forthe perpetrators because there are no strict sanctions for the perpetrators. the obstacles facedby law enforcers are divided into 2 factors, namely internal factors and external factors. Theseobstacles are in the form of: a lack of Inhu Resort Police personnel, communityculture/customs, lack of funds and facilities and infrastructure of the Inhu Resort Police. Inorder to investigate the crime of palm oil theft in the Inhu Resort police area, the Inhu ResortPolice made several efforts, namely, adding Inhu Resort Police personnel, collaborating withpalm oil companies in Inhu District and also the community and minimizing the use of fundsand utilizing existing facilities and infrastructure. Author's Suggestion, First, The Inhu ResortPolice as the front guard in law enforcement, in this case the investigation of criminal acts inInhu District, the Police must work together and improve quality in dealing with any existingcriminal acts. Second, to the public to be willing to report the perpetrators of the crime of palmoil theft in Inhu District to the Inhu Resort Police. Third, to the palm oil entrepreneurs in InhuRegency to further enhance their cooperation with the Inhu Resort Police and carry out therecommendations given by the Inhu Resort Police.Keywords: Law Enforcement-Palm Oil Theft-Polres Inhu